Semiconductor Technologies - Grym, Jan (IntechOpen, 2010)
Semiconductor technologies continue to evolve and amaze us. New materials, new structures, new manufacturing tools, and new advancements in modelling and simulation form a breeding ground for novel high performance electronic and photonic devices. This book covers all aspects of semiconductor technology concerning materials, technological processes, and devices, including their modelling, design, integration, and manufacturing.